Challenges and limitation of wearable sensors used in firefighters' protective clothing. (May 2022) - Shakeriaski, Farshad; Ghodrat, Maryam
This review aims to present recent improvements and existing challenges in the design of wearable sensors used in the firefighters' protective clothing. Wearable sensors are generally used directly on the body or placed on wearable items to monitor data for the safety of firefighters. Recently, wearable sensors have attracted much attention from researchers and experts. Most investigations have addressed novel designs for wearable sensors to enhance firefighters' safety measures and reduce the risk of exposure to fires. This article is an attempt to review design limitations of wearable sensors for future developments and improve existing shortcomings. The growing body of knowledge focused on the application of wearable technology to monitor firefighters' activity, health, and body temperature. In the following, we have discussed the trials of the design of the existing sensors. Finally, moisture and radiation as common exterior parameters in fire events are discussed which received less attention and have major impact on the performance of firefighters' wearable sensors.